Agentes públicos na segurança privada: a configuração do bico na cidade de Fortaleza - Silva, Antônio Marcos de Sousa (2010)
The present reseach has the aim of analyzing the configuration of odd jobs on private security of military policemen in the city of Fortaleza. With this in mind, a panorama of this activity was traced in order to enumerate the three recurrent characteristics of the odd jobs in Fortaleza, such as: security activities icommercial establishments (concert houses, beach huts, restaurants, beauty salons, markets, among others), private security (of businessmen or merchants) and, finally, the veiled odd job (to perform private patrolling while on duty, giving more attention to specific commercial points). The work revealed that this practice in Fortaleza is sustained both by the military officers and the privates and showed that both form networks of intermediaries or middlemen who sell security to businessmen or merchants. The research also dealt with the strict relationship between violence and the expansion of odd jobs through the city, denouncing the intensification of a culture of fear based on the feeling of insecurity. At last, the work dealt with the implications of this activity for military policemen due to their disciplinary and ethics code. The discussion ended also with the relationship between the precariousness of the police work and the work on private security.